The Application of Islamic Law to Improve Cultivating Humanity in Indonesia in Terms of Multicultural Fiqh - Nur Salsabil Juventania Syahputri; Sayyaf, R. Tanzil Fawaiq (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The creation of this paper aims to find out how the efforts of Islamic law in improving the cultivation of humanity of society in Indonesia in terms of multicultural fiqh. To be able to achieve this goal, this article is written using the library research method, this article has three problems that will be discussed later, namely, what is meant by cultivating humanity, understanding multicultural fiqh, and how Islamic law efforts in increasing cultivate humanity Indonesian society according to the perspective of multicultural fiqh. In general, many researchers emphasize observations on general problems, while the problems written in this article have not been raised as objects of research before. So, this article is considered necessary to be made as a first step in reviewing the above problems. The topic of this problem is interesting to discuss because there are not many journal articles that discuss cultivating humanity in the scope of multiculturalism and multicultural fiqh, most previous researchers discussed general discussions and only focused on conflict management and education. This article provides new ideas on efforts to increase cultivating humanity in Indonesian society which highly upholds cultural heritage values but is associated with multicultural fiqh in solving issues that occur amid society.